1995
DOI: 10.1029/94ja02703
|View full text |Cite
|
Sign up to set email alerts
|

Observations of mirror waves and plasma depletion layer upstream of Saturn's magnetopause

Abstract: The two inbound traversals of the Saturn's magnetosheath by Voyagers 1 and 2 have been studied using plasma and magnetic field data. In a great portion of the subsolar magnetosheath, large‐amplitude compressional waves are observed at low frequency (∼0.1 fp) in a high‐β plasma regime. The fluctuations of the magnetic field magnitude and ion density are anticorrelated, as are those of the magnetic and thermal pressures. The normals to the structures are almost orthogonal to the background field, and the Doppler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 21 publications
3
47
1
Order By: Relevance
“…The plasma density decreases and magnetic field strength increases within it. An investigation of Cassini measurements in Saturn's magnetosheath by Masters et al (2014) found that in this case there is no difference in the plasma depletion layer for northward and southward IMF, which is contrary to the results of related Voyager measurements that indicated an IMF effect (Violante et al, 1995). Masters et al (2014) inferred that reconnection at the dayside magnetopause is not effective at Saturn.…”
Section: Southward and Northward Imfcontrasting
confidence: 44%
“…The plasma density decreases and magnetic field strength increases within it. An investigation of Cassini measurements in Saturn's magnetosheath by Masters et al (2014) found that in this case there is no difference in the plasma depletion layer for northward and southward IMF, which is contrary to the results of related Voyager measurements that indicated an IMF effect (Violante et al, 1995). Masters et al (2014) inferred that reconnection at the dayside magnetopause is not effective at Saturn.…”
Section: Southward and Northward Imfcontrasting
confidence: 44%
“…Mirror mode structures have been detected in the magnetosheaths of the Earth, Jupiter and Saturn (Tsurutani et al, 1982(Tsurutani et al, , 1984Balogh et al, 1992;Violante et al, 1995;Bavassano Cattaneo et al, 1998;Baumjohann et al, 1999;Lucek et al, 1999;Soucek et al, 2008;Balikhin et al, 2009). They are characterized by small or no changes in the magnetic field across the structures, with scale of tens of proton gyroradii.…”
Section: Introductionmentioning
confidence: 99%
“…Different mirror mode intervals with B and D pointing in different directions will yield estimates for all offset components O x , O y , and O z . Furthermore, mirror modes are not restricted to the Earth's magnetosheath but have also been observed in other solar system environments (e.g., Russell et al, 1989;Glassmeier et al, 1993;Violante et al, 1995;Schmid et al, 2014). Hence, magnetic field measurements in distant regions of the solar system may benefit from offset determinations by the mirror mode method, as well.…”
Section: Discussionmentioning
confidence: 99%